Who was Arnobius the Younger? Dissimulation, Deception and Disguise by a Fifth-Century Opponent of Augustine. Issue 2 (3rd April 2018) - JAMES, N. W.
Abstract : Twentieth-century scholars believed that Arnobius the Younger was an African monk living in Rome. This is untenable. There is now considerable doubt over the authorship of several works ascribed to him by Germain Morin: the Expositiunculae has been proved to date from the early medieval period, but the author of the anti-predestinarian Commentarii in Psalmos, one 'Arnobius', is also responsible for writing the mid fifth-century Praedestinatus, an attack on Augustine's predestinarian theology and its champion, Prosper of Aquitaine. The content of these works and related evidence point to Julian of Eclanum as the true author.